The Effect of Using the Problem Based Instruction Learning Model Aided by Media Posters on the Learning Outcomes of Class VIII Students of SMP Negeri 5 Umbu Ratu Nggay - Sepri Tay Bohi; Yohana Makaborang; Yohana Njoroemana (Formosa Journal of Multidisciplinary Research, 2023)
The purpose of this study was to determine the effect of using the problem-based instruction model assisted by poster media on the learning outcomes of class VIII students at SMP Negeri 5 Umbu Ratu Nggay. This type of research is a type of experimental research, using an infact-group comparison research design. The total population is 54 people consisting of two classes, namely class VIII A totaling 27 people and class VIII B totaling 27 people. The sampling technique used is total sampling, namely the entire population is used as a sample. The method used to collect data is the test method. The data will be processed through statistical calculations and average correlation using SPSS. The results of the study obtained a tcount value of 7.250, indicating a positive influence from the use of the problem based instruction learning model assisted by poster media on the learning outcomes of class VIII students at SMP Negeri 5 Umbu Ratu Nggay.